Drug-Induced Liver Injury Associated with Turmeric and Piperine: A Case and Review - Atul Shrestha; Sarah Elliott; Joshua Haron Abasszade; Kyle Wu; Thomas Worland; Ian Simpson; Anouk Dev (Case Reports in Gastroenterology)
Introduction: Turmeric is a common spice used in traditional Chinese and Ayurvedic medicine for a variety of purported health benefits. Recent concerns have arisen regarding turmeric-induced liver injury linked to formulations with enhanced bioavailability, often including piperine found in black pepper. Case Presentation: We explore a case of a 40-year-old female with increasing fatigue, pruritus, and dark urine following consumption of turmeric and black pepper “wellness shots” leading to a significant drug-induced liver injury. Conclusion: This case underscores the critical need to recognise herbal remedies, such as turmeric, as potential sources of hepatotoxicity. Despite a reputation of safety, limited regulation and testing of turmeric may mean potential adverse effects are under-recognised. Understanding the mechanisms behind turmeric and black pepper’s hepatotoxicity, including the role of potential genetic predispositions, requires further investigation for its safe use.